Video segments: A valuable tool for teaching English phonological processes - Blázquez, Bettiana Andrea (Argentinian Journal of Applied Linguistics - ISSN 2314-3576, 2021)
This article explores the advantages of using authentic video segments - scenes, previews, documentaries, shorts and commercials- when teaching English phonological processes. The first section provides a possible classification of this type of audiovisual material and a description of its potential. Then, it offers a definition of phonological processes and a plausible typology. Finally, a framework for structuring a video lesson is outlined. In the second part two sets of sample activities, which have been designed on the basis of this framework, are shared and described. The overall aim of these worksheets is to view them as springboards for designing new activities in terms of other learning purposes. The employment of video segments will encourage learners to recognise phonological processes, develop their listening skill and extend their learning beyond the classroom.